Controlling land use sprawl with geospatial indices for effective local government - Rusni, Nur Aulia; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias (KAED Universal Design Unit Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Controlling the land use sprawl and managing the rapid urban growth process has become key issues for local government agencies in many developing countries including Malaysia. This paper intended to review and examined the core problems of land use sprawl control with local planning policies and the agencies that involve in implementing these processes. Many types of research have been conducted to measure urban sprawling which includes the usage of spatial Indices with GIS and remote sensing techniques. But many of the existing researches has been acknowledging to have left out the local planning policies perspective which create conflicts of interest with the local government, developers, stakeholders and the community of the particular area. In order to avoid this issues, this paper attempts to integrate the local planning policy into the geospatial indices measurement so the end result will be useful for the local government and other stakeholders.